The foundations of the Aarhus Convention - Barritt, Emily (London [England] : Hart Publishing, 2020)
"This important new monograph offers an innovative new analysis of the Convention. Environmental law is dense with monolithic concepts, from environmental democracy to intergenerational justice, from sustainable development to stewardship. Each concept generating its own mythology about what environmental law should aspire to. Sometimes these ideas become so big that we lose hold of their meaning and therefore what we allude to when we describe environmental law in such terms. No more so is this true than in relation to the Aarhus Convention, an ambitious instrument of environmental law that promotes public participation and access to justice in relation to the environment. Since its inception it has been revered in glowing terms, praised variously for its contribution to citizenship, environmental responsibility and democratic legitimacy. But how are we to know whether these descriptions are mere puffs or genuine statements about the Convention's character. This book digs deep into the foundations of the Aarhus Convention, illuminating its ambitious potential through the lens of three foundational purposes - environmental rights, democracy, and stewardship. In so doing, it both contributes to our understanding of the Convention and our understanding of three important purposes that inhabit environmental law, unravelling and reassembling them to build meaning into our broad-brush descriptions"--
The philosophical scope of the Aarhus Convention -- The three purposes -- Environmental democracy -- Environmental rights -- Environmental stewardship -- Interpretive possibilities.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Convention on Access to Information, Public Participation in Decision-making, and Access to Justice in Environmental Matters -- (1998 June 25); Environmental law; Environmental justice; Environmental protection; Freedom of information; Environmental law, International; International environmental law; Electronic books